Effects of the Response Requirement on Rats' Choice between Probabilistic Reinforcers. - Yáñez, Nataly; Bouzas, Arturo; Segura, Alejandro (Psychological Record, 2023)
Subjects persist more or wait out delays longer than optimal, given the reward structure of the environment, the availability of information about the past and the future, and the certainty about the consequences. Evaluating whether animals estimate the value of uncertain consequences based on an effort already spent is critical to revealing the mechanisms and rules organisms use to choose under uncertainty. To explore the effects of the effort investment on uncertain environments, we evaluated rats on a discrete-trials choice procedure in which they had to fulfill a response requirement to reach the choice point. Subjects had to choose between alternatives with equal reinforcement probabilities (both.50) in some conditions or different reinforcement probabilities (.25 vs..75) in other conditions. In addition, we separated the response requirement and choice phases to favor the discrimination between the prior investments and the prospects of the current choice. We manipulated the reinforcement probabilities, the presence or absence of the response requirement (R), and the alternative on which the rats had to fulfill the requirement; it was on one alternative (Experiment 1) or both alternatives (Experiment 2). In both experiments, the reinforcement probability of each alternative guided the rats' choice, not past effort. Separating the effort phase from the choice phase could change the investment context, leading the animals to focus on the consequences and not integrate the effort already done into the alternatives' value.